Carotenoids 2017
DOI: 10.5772/67724
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Stress toward Carotenogenesis Regulatory Mechanism through In Vitro Model System

Abstract: Carotenoid biosynthesis is influenced by some aspects and is liable to geometric isomerisation with the existence of oxygen, light, and heat, which affect color degradation and oxidation. The major problems related to carotenoid accumulation inherently originate from pigment instability. This chapter discusses an overview on the influence of stringent control of genetic, developmental, and environmental factors toward carotenoid biogenesis in potato minitubers through the potential model system for rapid initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Besides their importance in photosynthetic tissues, carotenoids also serve as precursors for two phytohormones (abscisic acid and strigolactones) and several apocarotenoids and some of them also exhibit strong aroma properties. The accumulation of carotenoids and their stability in plant tissues are affected by several factors such as light, temperature, water stress, and pH [56,57] Even if we observed a decrease of carotenoids concentration after borage treatments, no damage in photosynthetic apparatus resulted from the analysis of chlorophyll fluorescence indexes. Indeed, the performance index (PI) and the quantum maximum efficiency of PSII (Fv/Fm) were similar to those of control plants and Fv/Fm values were always higher than 0.83, commonly considered as a threshold between stressed and non-stressed leaves.…”
Section: Discussionmentioning
confidence: 58%
“…Besides their importance in photosynthetic tissues, carotenoids also serve as precursors for two phytohormones (abscisic acid and strigolactones) and several apocarotenoids and some of them also exhibit strong aroma properties. The accumulation of carotenoids and their stability in plant tissues are affected by several factors such as light, temperature, water stress, and pH [56,57] Even if we observed a decrease of carotenoids concentration after borage treatments, no damage in photosynthetic apparatus resulted from the analysis of chlorophyll fluorescence indexes. Indeed, the performance index (PI) and the quantum maximum efficiency of PSII (Fv/Fm) were similar to those of control plants and Fv/Fm values were always higher than 0.83, commonly considered as a threshold between stressed and non-stressed leaves.…”
Section: Discussionmentioning
confidence: 58%
“…Seasonal differences, growing conditions, locations, genotypes and postharvest storage conditions are among the factors that can be significantly affect the quality and nutritional value of plants [19][20][21][22]. The bioavailability of carotenoids is a complex issue and depends on many factors [23]. In this study of environment and genotype interactions, the data revealed that variations in total carotenoid content and the concentration of individual carotenoid pigments is due to strong relationship between genotype and plant group.…”
Section: Resultsmentioning
confidence: 82%
“…Zeaxanthin level decreases as the light decreases. [51,52] This suggests that in countries with a longer period of solar radiation and intensity, the content of apocarotenoids is higher. Various publications confirm that the accumulation of carotenoids appears to be determined by the physiological, genetic, and biochemical characteristics of the plant species, as well as environmental growth factors, such as air temperature, light intensity, and photoperiod.…”
Section: Influence Of Environmental Factors On Saffron Components Bio...mentioning
confidence: 99%